Musical abilities in the perspective of music psychology – evolution of ideas - Kamińska, Barbara (Studia Psychologica: Theoria et praxis, 2002)
The author focuses on the problem of aural musical abilities (musical ear) and outlines the evolution of ideas on their structure, inheritance, prevalence and developmental potential. She begins her review with the considerations of Michaelis (1805) and the early empirical studies of Seashore (1919) and ends with the latest studies conducted within three different paradigms: 1) the cognitive psychology of music and musical psycho-acoustics; 2) neurobiological brain studies 3) the "musical meaning" approach inspired by neurolinguistics and cultural anthropology.